X-shooting ULLYSES: massive stars at low metallicity : IV. Spectral analysis methods and exemplary results for O stars - Sander, Andreas A. C.; Bouret, J.-C.; Bernini Peron, Matheus; Puls, J.; Backs, F.; Berlanas, S. R.; Bestenlehner, J. M.; Brands, S. A.; Herrero, A.; Martins, F.; Maryeva, O.; Pauli, D.; et al. (Astronomy and astrophysics, 2024)
Context. The spectral analysis of hot, massive stars is a fundamental astrophysical method of determining their intrinsic properties and feedback. With their inherent, radiation-driven winds, the quantitative spectroscopy for hot, massive stars requires detailed numerical modeling of the atmosphere and an iterative treatment in order to obtain the best solution within a given framework. Aims. We present an overview of different techniques for the quantitative spectroscopy of hot stars employed within the X-Shooting ULLYSES collaboration, ranging from grid-based approaches to tailored spectral fits. By performing a blind test for selected targets, we gain an overview of the similarities and differences between the resulting stellar and wind parameters. Our study is not a systematic benchmark between different codes or methods; our aim is to provide an overview of the parameter spread caused by different approaches. Methods. For three different stars from the XShooting ULLYSES sample (SMC O5 star AzV 377, LMC O7 star Sk -69° 50, and LMC O9 star Sk-66° 171), we employ different stellar atmosphere codes (CMFGEN, Fastwind, PoWR) and different strategies to determine their best-fitting model solutions. For our analyses, UV and optical spectroscopy are used to derive the stellar and wind properties with some methods relying purely on optical data for comparison. To determine the overall spectral energy distribution, we further employ additional photometry from the literature. Results. The effective temperatures found for each of the three different sample stars agree within 3 kK, while the differences in log g can be up to 0.2 dex. Luminosity differences of up to 0.1 dex result from different reddening assumptions, which seem to be systematically larger for the methods employing a genetic algorithm. All sample stars are found to be enriched in nitrogen. The terminal wind velocities are surprisingly similar and do not strictly follow the u∞−Teff relation. Conclusions. We find reasonable agreement in terms of the derived stellar and wind parameters between the different methods. Tailored fitting methods tend to be able to minimize or avoid discrepancies obtained with coarser or increasingly automatized treatments. The inclusion of UV spectral data is essential for the determination of realistic wind parameters. For one target (Sk -69° 50), we find clear indications of an evolved status.